촉매 제조방법에 따른 Co-CeO₂ 촉매의 N₂O 분해 특성 연구 - 김혜정(Hye Jeong Kim); 김민재(Min-Jae Kim); 이승재(Seung-Jae Lee); 유인수(In-Soo Ryu); 이광복(Kwang Bok Yi); 전상구(Sang Goo Jeon) (Clean Technology, 24(3), 2018)
본 연구는 Co-CeO2 촉매의 N2O 분해 반응에서 촉매의 제조 방법이 활성에 미치는 영향을 고찰하였다. Co-CeO2 촉매는 공침법(Co-precipitation)과 함침법(Incipient wetness impregnation)으로 제조하였다. 제조된 촉매의 성능을 평가하기 위하여N2O 직접 촉매 분해(Direct catalytic N2O decomposition) 반응을 250 ~ 375 ℃에서 실시하였다. 그 결과 공침법으로 제조된촉매(CoCe-CP)는 O2 및/또는 H2O의 존재 하에서도 N2O 분해 반응에서 향상된 성능을 보인 반면에 함침법으로 제조된 촉매(CoCe-IM)는 그렇지 못하였다. 이러한 촉매 활성의 차이를 조사하기 위하여 XRD, BET, TEM, H2-TPR, O2-TPD 그리고 XPS 와 같은 촉매 특성 분석들을 진행하였다. 촉매의 제조 방법에 따라서 입자의 크기 및 표면적이 변화하는 것을 확인하였고 합성 과정이 촉매의 물리적 특성에 영향을 미치는 것을 알 수 있었다. 공침법으로 제조된 촉매의 활성 증가는 Co3+ → Co2+의향상된 환원 특성 및 산소 탈착 속도 향상에 기인한 것으로 여겨진다. 하지만, N2O 분해와 관련이 있는 촉매의 표면 전하 상태 및 결합에너지는 제조 방법에 따라서 변하지 않는 것을 확인하였다. This study investigated the influence of catalyst preparation on the activity of Co-CeO2 catalyst for N2O decomposition. Co-CeO2 catalysts were synthesized by co-precipitation and incipient wetness impregnation. In order to estimate the performance of the as prepared catalysts, direct catalytic N2O decomposition test was carried out under 250 ~ 375 ℃. As a result, the catalyst prepared by co-precipitation (CoCe-CP) showed an enhanced performance on N2O decomposition reaction even in the presence of O2 and/or H2O, whereas the impregnation catalyst (CoCe-IM) did not. In order to investigate the difference in catalytic activity, characterization such as XRD, BET, TEM, H2-TPR, O2-TPD, and XPS was conducted. It is confirmed that the particle size and specific surface area were changed depending on the catalyst preparation method and the synthesis process influenced the physical properties of the catalysts. In addition, the improvement in the activity of the catalyst prepared by co-precipitation is due to the enhanced reduction from Co3+ to Co2+ and the improved oxygen desorption rate. However, it has been confirmed that the surface electron state and binding energy, which are related to N2O decomposition, do not change depending on the preparation method. KCI Citation Count: 1